2022
DOI: 10.3389/fonc.2022.759153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Circadian Rhythms on the Development and Clinical Management of Genitourinary Cancers

Abstract: The circadian system is an innate clock mechanism that governs biological processes on a near 24-hour cycle. Circadian rhythm disruption (i.e., misalignment of circadian rhythms), which results from the lack of synchrony between the master circadian clock located in the suprachiasmatic nuclei (SCN) and the environment (i.e., exposure to day light) or the master clock and the peripheral clocks, has been associated with increased risk of and unfavorable cancer outcomes. Growing evidence supports the link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…Similar light therapy approaches have been shown to improve mood outcomes, perhaps via improved circadian entrainment, in patients undergoing autologous stem cell transplantation hospitalization for the treatment of multiple myeloma ( Valdimarsdottir et al, 2018 ). Light therapy has also shown promise as a means for improving circadian entrainment and outcomes in the clinical management of genitourinary cancers ( Kaur et al, 2022 ). There is no reason to presume that light therapy could not also be used to improve outcomes in patients experiencing perioperative circadian disruption and POCD resulting from cardiac surgery.…”
Section: Hospital Light Interventions For Sleep and Circadian Healthmentioning
confidence: 99%
“…Similar light therapy approaches have been shown to improve mood outcomes, perhaps via improved circadian entrainment, in patients undergoing autologous stem cell transplantation hospitalization for the treatment of multiple myeloma ( Valdimarsdottir et al, 2018 ). Light therapy has also shown promise as a means for improving circadian entrainment and outcomes in the clinical management of genitourinary cancers ( Kaur et al, 2022 ). There is no reason to presume that light therapy could not also be used to improve outcomes in patients experiencing perioperative circadian disruption and POCD resulting from cardiac surgery.…”
Section: Hospital Light Interventions For Sleep and Circadian Healthmentioning
confidence: 99%
“…BPH is the most common urological disease in men over 50 years of age and affects bladder voiding [ 4 ]. Although associations between the circadian clock and the pathogenesis of prostate cancer are elucidated in the basic and clinical literature [ 19 , 20 ], the relationships among Bmal1 signaling, BPH and prostate cancer remain for future research to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…While circadian disruption caused by, e.g., night shift work, can increase the incidence of cardiovascular events, original research indicated that night shift contributed to the disruption of circadian protein expression in breast tissue suggesting a contribution to cancer development. Indeed, it is now established that disruption of circadian rhythms plays a key role in tumorigenesis and facilitates the development of cancer ( 32 - 38 ) and that pharmacological modulators of the circadian clock could be potentially therapeutic ( 39 ). Here, circadian-based treatments could modulate the pharmacological ability of anti-cancer drugs towards improving therapeutic outcomes and be potentially incorporated into clinical trials for treatment optimization and improved patient survival.…”
Section: Genetic Underpinnings Of Circadian Rhythmsmentioning
confidence: 99%